1999
DOI: 10.1097/00004647-199902000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Neuropeptide Y Receptors mRNA and Protein in Human Brain Vessels and Cerebromicrovascular Cells in Culture

Abstract: Neuropeptide Y (NPY) has been suggested as an important regulator of CBF. However, except for the presence of Y1 receptors in large cerebral arteries, little is known about its possible sites of action on brain vessels. In this study, we sought to identify the NPY receptors present in the human cerebrovascular bed. Specific Y1 receptor binding sites, localized on the smooth muscle of human pial vessels and potently competed by NPY, polypeptide YY (PYY), and the selective Y1 receptor antagonist BIBP 3226, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…In contrast, the failure of CCK to alter microvascular tone correlated well with the lack of CCK receptor expression in microvascular smooth muscle, suggesting that this peptide is unlikely to directly couple flow to neuronal activity. We found that NPY induced contraction of intracortical microvessels consistent with contractile NPY-Y1 receptor mRNAs (Abounader et al, 1999) and proteins (Bao et al, 1997) in cortical microarterioles. Intracortical microvessels were also highly responsive to the NO donor DEA NONOate, further emphasizing the opposite vasomotor role of colocalized NO and NPY (ϮSOM) within cortical interneurons.…”
Section: Vasoactive Mediatorssupporting
confidence: 67%
See 3 more Smart Citations
“…In contrast, the failure of CCK to alter microvascular tone correlated well with the lack of CCK receptor expression in microvascular smooth muscle, suggesting that this peptide is unlikely to directly couple flow to neuronal activity. We found that NPY induced contraction of intracortical microvessels consistent with contractile NPY-Y1 receptor mRNAs (Abounader et al, 1999) and proteins (Bao et al, 1997) in cortical microarterioles. Intracortical microvessels were also highly responsive to the NO donor DEA NONOate, further emphasizing the opposite vasomotor role of colocalized NO and NPY (ϮSOM) within cortical interneurons.…”
Section: Vasoactive Mediatorssupporting
confidence: 67%
“…To assess whether or not cortical microvessels could potentially respond to perivascularly released neuropeptides from the identified GABA interneurons, we assessed, by RT-PCR, the expression of receptors for these peptides. Expression of receptors for VIP, CCK, and SOM was determined in human cerebromicrovascular endothelial (EC), smooth muscle (SMC), and fetal astroglial (AST) cell cultures generated as described previously (Abounader et al, 1999). The following primer pairs were used (receptor: GenBank accession number, primers, and length of PCR product): VPAC1: NM_004624.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Y1, Y2, and Y5 receptor are also expressed by macrophages, with different functions for these receptors in the macrophage response to NPY (11). Only one receptor, Y1, is expressed by capillary endothelia (1,17). Surprisingly, mRNA expression levels of Y1, Y2, and Y5 were not altered during BE infection ( Table 2).…”
Section: Fig 9 Influence Of Npy Deficiency On Virus Levels In the Cmentioning
confidence: 99%